Use of intrathecal baclofen administered by programmable infusion pumps in resistent spasticity. (1989)
On the basis of previous experimental and clinical studies1,2 patients with severe spasticity due to spinal cord damage from multiple sclerosis in 8 cases and postraumatic paraplegia in 6 and resistent to all conservative treatments were selected for a trial with morphine and baclofen administered intrathecally through a catheter placed in the spinal subarachnoid space rostral to the affected segments and attached to a subcutaneous reservoir. Whereas morphine single injection did not show any benefit, baclofen bolus injection 30 to 60 ?g, revealed a marked decrease of spasticity and associated symptoms in 8 cases. After checking the clinical effect during 3 weeks and changes in electroneurophysiological studies and bladder manometry the catheter was attached to a subcutaneous programmable pump able to be refilled percutaneously and administered baclofen continuously or more often following a multistep complex programme in total doses of 90 to 150 ?g per day. After a mean follow-up of 5 months all cases showed an absence of spasms and pain, a notable improvement for bettering of sphincter functions and a marked muscle relaxation that improves motor capacity, leading to increased ambulation or mobility. Neither complications nor side-effects were observed.